Souveraineté et fédéralisme - Rémillard, Gil (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1979)
The notion of sovereignty is the most fundamental concept of public law. At the same time, it is one of the main difficulties federalism has to face. Where does sovereignty reside in a federal state ? While this question is not an easy one to answer, knowledge of the manner in which it has been answered in Canadian constitutional law is essential to an understanding of the present constitutional crisis. The most appropriate definition of sovereignty is « jurisdiction to define jurisdictions ». This definition implies the concept of an ultimate authority and its application to a federal system is of great difficulty. Two main theories confront each other. The first one develops the concept that sovereignty should be shared between the federal government and the federated states. The second sees sovereignty as belonging exclusively to the federal government, regional governments merely enjoying some form of autonomy. This paper studies the implications of both theories in Canadian federalism.